Tense and Discourse Structure: The Timeline Hypothesis. Issue 9 (21st October 2021) - Göbel, Alexander; Frazier, Lyn; Clifton, Charles
ABSTRACT: Recent studies of appositives have turned up differences between sentence-medial appositives and sentence-final appositives, for instance, in their availability for discourse continuations. Three experiments investigated whether medial appositives are more difficult to comprehend than final appositives and if so why. Experiment 1 tested coordinating (Narration) versus subordinating (Elaboration) discourse relations in sentence-medial or sentence-final position. Coordinating relations received lower naturalness ratings in general but especially in medial position. We propose a timeline hypothesis that coordinating (Narration) relations in medial position are difficult because the processor constructs a narrative timeline from earlier to later times and avoids ordering an event later on the timeline than an event whose description has not yet been completed. An interpretation study of ambiguous appositives confirmed the timeline hypothesis (Experiment 2). In Experiment 3, the appositive event was disambiguated to either precede or follow the main clause event on the narrative timeline. Sentences with medial appositives disambiguated to precede the main clause event received higher naturalness ratings than those disambiguated to follow the main clause event, as expected on the timeline hypothesis.